An introduction to sieve methods and their applications - Cojocaru, Alina; Murty, Maruti Ram.; London Mathematical Society (Cambridge, UK ; New York : Cambridge University Press, 2005)
This book provides a motivated introduction to sieve theory. Rather than focus on technical details which obscure the beauty of the theory, the authors focus on examples and applications, developing the theory in parallel. Suitable for a senior level undergraduate course or an introductory graduate course in analytic number theory.
Cover; Half-title; Series-title; Title; Copyright; Dedication; Contents; Preface; 1 Some basic notions; 2 Some elementary sieves; 3 The normal order method; 4 The Turán sieve; 5 The sieve of Eratosthenes; 6 Brun's sieve; 7 Selberg's sieve; 8 The large sieve; 9 The Bombieri-Vinogradov theorem; 10 The lower bound sieve; 11 New directions in sieve theory; References; Index.
Includes bibliographical references (pages 218-221) and index.
Print version record.
Keywords: Sieves (Mathematics); MATHEMATICS -- Number Theory; Sieves (Mathematics); Electronic books